Question

# If α,β and γ are the roots of the equation x3 + 2x2 + 3x + 1 = 0. Find the constant term of the equation whose roots are 1β3 + 1γ3 - 1α3, 1γ3 + 1α3 - 1β3 , 1α3 + 1β3 - 1γ3. __

Solution

## x3 + 2x2 + 3x + 1 = 0 x3 + 1 = -(2 x2 + 3x) ...................(1) Cubing on both sides (x3+1)3 = - (2x2+3x)3 x9 + 3x6 + 3x3 + 1 = -[8x6 +27x3 + 18x3(2x2 + 3x))] x3 + 1 = -(2x2 + 3x from equation 1). x9 + 3x6 + 3x3 + 1 = -[8x6 + 27x3 + 18x3(-x3 -1)] Putting x3 = y in this equation y3 + 3y2 +3y + 1 = -[8y2 +27y + 18y (- y - 1)] y3 - 7y2 +12y + 1 = 0 {its root α3, β3, γ3}_____________(2) Changing y to 1y in equation 2 1y3 - 7y2 + 12y + 1 = 0 y3 + 12y2 - 7y + 1 = 0 ____________(3) If roots are {1α3, 1β3, 1γ3} Let  1α3 = a, 1β3 = b, 1γ3 = c a + b + c = -12 1β3 + 1γ3 - 1α3 = (a + b + c) - 2a = -12 - 2y y = 12+p2 Putting the value of y in equation 3 -(12+p)38 + 12 (12+p)24 + 7 (12+p)2 + 1 = 0 (12+p)3 - 24(12+p)2 - 28(12 + p) - 8 = 0 p3 + 12p2 - 172p - 2072 = 0 Change the variable x in place of p x3 + 12x2 - 172x - 2072 Constant term = -2072

Suggest corrections